2005
DOI: 10.3168/jds.s0022-0302(05)72664-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Feeding and Drinking Patterns of Dairy Cows in Two Cow Traffic Situations in Automatic Milking Systems

Abstract: With increasing possibilities for obtaining online information for individual cows, systems for individual management can be developed. Feeding and drinking patterns from automatically obtained records may be valuable input information in these systems. With the aim of evaluating appropriate mixed-distribution models for feeding and drinking events, records of 30 fresh cows from visits at feeding stations (n = 83,249) and water bowls (n = 67,525) were analyzed. Cows were either allowed a high-milking (HF) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
35
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 15 publications
9
35
2
Order By: Relevance
“…The same models could be applied to cows on mixed diets with high or low forage-to-concentrate ratios (70) and with high or low protein content (69). These models have led to novel methods to analyze diurnal pat-terns in cow feeding behavior (70) and have successfully been applied to analyze data sets obtained with cows elsewhere (1,19,43,50,55).…”
Section: Resultsmentioning
confidence: 99%
“…The same models could be applied to cows on mixed diets with high or low forage-to-concentrate ratios (70) and with high or low protein content (69). These models have led to novel methods to analyze diurnal pat-terns in cow feeding behavior (70) and have successfully been applied to analyze data sets obtained with cows elsewhere (1,19,43,50,55).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, they tended to compensate the lower feed intake by visiting the feeders earlier the next morning. Other investigators indicated that initiation of a new meal correlates positively with the time since the last meal and negatively with the amount of feed consumed on that meal (Tolkamp et al, 2002;Melin et al, 2005).…”
Section: Feed Intake Feeding Patterns and Selective Consumption Of Tmentioning
confidence: 97%
“…Meal criteria (i.e., minimum time interval that a cow was away from the feeder to be considered a meal) were determined for each cow and treatment separately by fitting log-transformed individual intervals (i.e., an interval is the time between two adjacent visits) collected for 6 days to a mixture of Gaussian and Weibull (G-W) distribution using PROC IML (SAS, 2001), as outlined by Melin et al (2005). Individual meal criteria were used to calculate the daily number of meals per cow.…”
Section: Data Handling and Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowering the dispensation rate might hinder the gaining of leftovers (Konggaard, 1980). A gate at the back of the feeder could also be used to restrain butting (Melin et al, 2005). More studies are needed to solve the problems of disturbing and stealing at the concentrate self-feeder.…”
Section: Cowsmentioning
confidence: 97%